2021
DOI: 10.1016/j.mayocp.2021.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in Health and Disease: A State-of-the-Art Review

Abstract: Eosinophils play a homeostatic role in the body's immune responses. These cells are involved in combating some parasitic, bacterial, and viral infections and certain cancers and have pathologic roles in diseases including asthma, chronic rhinosinusitis with nasal polyps, eosinophilic gastrointestinal disorders, and hypereosinophilic syndromes. Treatment of eosinophilic diseases has traditionally been through nonspecific eosinophil attenuation by use of glucocorticoids. However, several novel biologic therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
123
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 80 publications
2
123
0
6
Order By: Relevance
“…Eosinophil activation results in degranulation with release of various cytotoxic granular proteins including major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil peroxidase (EPO) and eosinophil-derived neurotoxin (EDN) ( Rothenberg and Hogan, 2006 ). However, recent findings increasingly point toward an important contribution of eosinophils to GI homeostasis ( Shah et al, 2020 ; Masterson et al, 2021 ; Wechsler et al, 2021 ). These novel roles include promoting the survival and class switching of immunoglobulin (Ig)A-producing plasma cells, supporting IL-1β-mediated IgA production, maintaining Th17 cell differentiation and supporting microbial homeostasis, mucus production and inflammatory homeostasis in the intestinal microenvironment ( Jung et al, 2015 ; Marichal et al, 2017 ).…”
Section: Intestinal Mucosal Eosinophils In Homeostasis and Inflammationmentioning
confidence: 99%
“…Eosinophil activation results in degranulation with release of various cytotoxic granular proteins including major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil peroxidase (EPO) and eosinophil-derived neurotoxin (EDN) ( Rothenberg and Hogan, 2006 ). However, recent findings increasingly point toward an important contribution of eosinophils to GI homeostasis ( Shah et al, 2020 ; Masterson et al, 2021 ; Wechsler et al, 2021 ). These novel roles include promoting the survival and class switching of immunoglobulin (Ig)A-producing plasma cells, supporting IL-1β-mediated IgA production, maintaining Th17 cell differentiation and supporting microbial homeostasis, mucus production and inflammatory homeostasis in the intestinal microenvironment ( Jung et al, 2015 ; Marichal et al, 2017 ).…”
Section: Intestinal Mucosal Eosinophils In Homeostasis and Inflammationmentioning
confidence: 99%
“…They combat several parasitic, bacterial, and viral infections by interacting with B cells, T cells, macrophages, and neutrophils. Eosinophils are further involved in the regulation of several diseases, including allergic asthma, esophagitis, myopathies, and autoimmune disorders due to directly or indirectly promoting tissue damage or altering the local immune status [14][15][16] . A recent study showed that upregulation of the eosinophil count in the peripheral blood is linked with a better prognosis and response to ICI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, resident and newly recruited eosinophils may respond to specific tissue requirements. This response implicates the regulation of immunoglobulin production, the promotion of both anti-and pro-inflammatory networks, tissue remodeling and repair, and modulation of epithelial barrier function at mucosal sites [6][7][8]. Notably, the gastrointestinal tract harbors the largest number of resident eosinophils in the body and eosinophilia and eosinophil activation are associated with gut dysfunction in a variety of inflammatory diseases, such as eosinophilic gastrointestinal diseases (EGIDs) and inflammatory bowel disease (IBD), and in other non-inflammatory entities, such as the disorders of brain-gut interaction (DBGIs).…”
Section: Introductionmentioning
confidence: 99%